AB0821 Analysis of organ damage in mixed connective tissue disease. (23rd January 2014) - Olesinska, M.; Czuszynska, Z.; Felis-Giemza, A.; Walkiewicz-Pielaszek, K.; Paradowska-Gorycka, A.; Rutkowska-Sak, L.; Marusak-Banacka, M.; Wiesik-Szewczyk, E.; Zdrojewski, Z.
Abstract : Background: Irreversible organ damage is a cause of mortality and morbidity in chronic inflammatory diseases. In most of them validated tools for disease damage assessment were prepared. There is no such a method in mixed connective tissue disease (MCTD). Objectives: To estimate disease damage by prepared method in MCTD. Methods: The wide range of clinical assessment of 69 MCTD patients (pts) was performed. Diagnosis was made based on Kasukawa's criteria. For assessment of damage extend we used index (DI) prepared for the study, based on SLICC/ACR DI, involving organs and systems affected on MCTD clinical course. To each organ involvement point scoring was added. To analyze correlation of DI with demographic and clinical variables Spearman's rank correlationwas used. Study was accepted by Local Ethics Committee. Results: Median of MCTD pts' age was 45 years (16 - 66), median of disease duration: 117, 8 months (10-420). Median of DI was 3, 0 (0- 12). The lowest values of DI: 0-2 were observed in 29 pts (42%), 3-6 in 31 patients (45%) and 7-10 in 7 pts (10%). The most often damage involved: skin, musculoskeletal, cardiovascular and pulmonary system. DI correlated with age of pts (R=0.426; P<0.001), disease duration (R=0.492; P<0.001), age at the diagnosis (R=0.296; P=0.015) and cumulative dose of corticosteroids (R=0.275; P=0.023). Conclusions: Our data confirm that the damage is a great concern in MCTD. Disease damage assessed by the method prepared in the study is related to age of pts, disease duration and cumulative corticosteroids dose. Disclosure of Interest: None Declared